Concentración mínima inhibitoria del extracto acuoso de Allium sativum en cepas de Candida albicans y Candida glabrata - Gaona Paccha, Ulises Armando (2021)
There is a great variety of plants that have antimicrobial properties, among them is garlic (Allium sativum), referred for a long time for its multiple properties, not only culinary, but also medicinal, particularly antimicrobial. The objective of this project was to evaluate the antifungal properties according to Kirby Bauer and the minimum inhibitory concentration (MIC) by the macrodilution technique of the aqueous extract of the “creole” variety of Allium sativum against Candida albicans and Candida glabatra. Candida species are recognized as the main cause of multiple skin and systemic infections, especially Candida glabrata reported with increasing frequency. For the extract, 100 grams of garlic bulbs, Creole variety, were crushed in a food processor with 40 ml of sterile distilled water; it was filtered through filter paper and subsequently centrifuged; 6 mm diameter discs of Whatman No. 3 filter paper were impregnated with this extract and sensitivity tests were carried out using the Kirby Bauer technique. The aqueous extract of Allium sativum, of the creole variety, is active, by the disk technique, against Candida albicans and Candida glabrata at a concentration of 8 160 μg / disk, while the MIC corresponds to a concentration of 3 187 μg / ml and which is also fungicidal. KEY WORDS: Aqueous extract, creole variety, macrodilution, MIC.